Analysis of students' errors in solving statistics problems based on Newman's Error theory: a study on high school students - Prameshti, Nhira L; Darmawan, Puguh; Dejarlo, Jenisus O. (Nashir Al-Kutub Indonesia, 2024)
This study analyzed the errors made by high school students in solving statistics problems based on Newman's Error Theory. Statistics is a complex topic that requires accuracy and precision, leading to frequent errors in problem-solving. This research employed a qualitative approach using test questions and interviews to identify the causes of errors. The research subjects were eleventh-grade students who met the criteria of making errors in the predetermined indicators. Data analysis was conducted through three stages: data reduction, data presentation, and conclusion drawing. The findings revealed that reading errors were minimal and did not significantly affect problem-solving, while comprehension errors occurred due to students’ lack of understanding of the problem statement. Transformation errors arose when students struggled to convert word problems into mathematical expressions, and process skill errors were observed when students performed incorrect calculations. Encoding errors occurred when students failed to write the final answer, provided incorrect final answers, or drew inaccurate conclusions. These findings indicated the need for targeted instructional strategies to address specific types of student errors. Teachers should have emphasized improving problem comprehension, enhancing mathematical translation skills, and strengthening students' ability to perform accurate calculations. By addressing these issues, educators could have supported students in developing a more structured and precise approach to solving statistical problems, ultimately improving their overall mathematical proficiency.